„Wielka akcja ratownicza" – działalność Polsko-Amerykańskiego Komitetu Pomocy Dzieciom (1919-1922) - Sochala, Magdalena (Acta Universitatis Lodziensis. Folia Historica, 2010)
In the first year of independence in Poland, social organisations and institutions in the helping children were operating with little help of the government. The organisations’ activity consisted mainly of food, clothes and shoes distribution as well as children supplementary alimentation and organising summer camps and summer play centres. This activity was called young generation biological rescue service initiative. Other countries and international organisations joined the children help activity. In 1919 the United States of America launched an initiative of food supply to the European countries affected by war, among others, to Poland. In 1918 Herbert Hoover was delegated to Europe. His mission aimed to establish the American Relief Administration (ARA). The key tasks of ARA operating in Poland since January 1919 was food distribution during 1920 and the first part of 1921 with the use of so called “food orders”, creation of a local organisation for “emergency products" distribution. The fundamental target was supplementary alimentation. A regular food portion distributed with minor changes in the years 1919-1922 was as follows: flour 62 g, beans 35 g, rice 20 g, milk 22 g, fat 10 g, sugar 15 g, cocoa 3 g; in total 167 g, 624 calories. This was a standard portion provided for children from 3 to 15 years of age. 2A of all food products were obtained from donations, and 'A was subsidised by the government. On 18 January 1920 as a result of concurrence of the activity of ARA and the Polish Children Relief Committee (Polski Komitet Pomocy Dzieciom) operating in Poland since 1919, the two organisations were joined and the Polish-American Children Relief Committee (Polsko- -Amerykanski Komitet Pomocy Dzieciom - PAKPD) was established. All in all, in the period from April 1919 to 1 May 1922, as much as 120,532,474 tons of food was distributed, worth 25,294,380 $, and clothes of the value o f 4,879,180 $, while the initiative cost 30,173,560 $. On 20 June 1922 ARA resigned from managing PAKPD, and the organisation remained an institution under Polish management financed from the state budget and self-governmental resources.